Analisis Penataan Ruang Ternak Sapi Potong di Kabupaten Lampung Utara sebagai Upaya Menunjang Ketahanan Pangan - Putra, Boby Arya (Jurnal Peternakan (Jurnal of Animal Science), 2023)
Livestock development is a series of continuous activities to develop the capabilities of farming communities, especially livestock communities, so that they are able to carry out productive businesses in the livestock sector independently. The livestock sub-sector has a strategic role in the development of the agricultural sector, namely in efforts to strengthen food security to meet animal protein needs, empower the community's economy, and can spur regional development. The development of the livestock sub-sector as an integral part of the agricultural sector needs special attention while still paying attention to the preservation of existing resources and the environment. This development effort cannot be separated from the availability of existing resources in the development area. However, it is still not optimal, because the causal factor is that the available land is not yet optimally utilized because it is only used for one type of farming business even though it can actually be used for integrated livestock farming. Meanwhile, the beef cattle development program is faced with the problem of increasingly narrow business land due to increasing competition in land use. However, the reality shows that with increasing population density, the land available for forage for livestock is increasingly narrowing, while feed is a component and key to the success of livestock production (Putra, 2021). It is not uncommon for livestock areas to be sacrificed because of the demand for this land for the development of certain sectors such as industry and residential areas, which have greater opportunities for short-term profits (Arfa'i, 2009). Continuous land conversion occurs due to the increasing need for land such as residential areas, industry, offices, tourist attractions, roads and other infrastructure to support community development. North Lampung Regency is one of the regencies in Lampung Province which has quite large potential in developing beef cattle farming. North Lampung Regency has quite an area of land, namely 2,726 km2. According to BPS North Lampung, in 2019, the recorded area of rice fields was 19,383 ha, the area of raw rice fields was eroded to 14,973 ha by 2021 (Central Statistics Agency, 2022). North Lampung Regency is also an area with quite a large livestock population, namely 32,490 heads (Central Bureau of Statistics, 2022). To develop the Beef Cattle business in a region, various information about the potential of the region, programs and activities that have been carried out, needs to be studied and analyzed so that the existing condition of the livestock can be accurately identified, and a better strategy for developing Beef Cattle can be formulated. in the future.